Spring Break in Chernobyl: Urbex, Apocalypse, and Materiality in Writing Classrooms - K Shannon Howard (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
The practice of urban exploration, or urbex—an activity in which we confront and document landscapes of ruin and make meaning from them—acts as a focal point through which students may investigate and write about the world surrounding them by gaining new perspectives of physical spaces and objects that often go ignored in daily living. More importantly, urbex inspires writing that responds to existing problems in our world (resource scarcity, lack of sustainability, and environmental trauma) while also helping students to conceptualize a better one.
Keywords: JAEPL